Mirabilis Jalapa L. Protein as Inductor of Apoptosis on UVB-induced Skin Damage in Mice (Bangladesh Journal of Medical Science, 2017)
Background: Mirabilis jalapa L. protein (MJ-Protein) has been shown to have antioxidant and anti-inflammatory effects in vitro. Thus, it has a potential protective effect against ultraviolet B (UVB)-induced skin damage.Objective: To determine the protective effect and mechanism of MJ protein in UVB-radiation exposed mouse skin.Methods: In this experimentalstudy, 30 female BALB/c mice aged 6 weeks were exposed to a single dose of UVB irradiation with 3 minimal erythema doses (MEDs) and continued with the treatment of 0.6 mg MJ-Protein topically. The number of apoptotic body (sunburn cells) formed in epidermal layers of mouse dorsal skin was assessed at 1, 24, 48, 72, 96 and 120h after UVB irradiation was compared to that of the control group. The difference in the sunburn cells number between two groups were analyzed using independent T-test with the level of significance of 0.05. The apoptosis mechanism was confirmed qualitatively by caspase-3 and DNA fragmentation analysis in vitro.Results:At 24 h after the UVB exposure (peak time for sunburn cells formation), there was a significant increase in the sunburn cells number in the group treated with topical application of MJ-Protein. There was increased caspase-3 expression and DNA fragmentation in HeLa cells treated with MJ-Protein.Conclusions: MJ-Protein protects againts UVB-induced skin damage in mice trough apoptosis induction.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.423-427